Synthesized effective atomic numbers for commercially available dual-energy CT - Kawahara, Daisuke (Rep Pract Oncol Radiother, 2020)
PURPOSE: The objective of this study was to assess synthesized effective atomic number (Z(eff)) values with a new developed tissue characteristic phantom and contrast material of varying iodine concentrations using single-source fast kilovoltage switching dual-energy CT (DECT) scanner. METHODS: A newly developed multi energy tissue characterisation CT phantom and an acrylic phantom with various iodine concentrations of were scanned using single-source fast kilovoltage switching DECT (GE-DECT) scanner. The difference between the measured and theoretical values of Z(eff) were evaluated. Additionally, the difference and coefficient of variation (CV) values of the theoretical and measured values were compared with values obtained with the Canon-DECT scanner that was analysed in our previous study. RESULTS: The average Z(eff) difference in the Multi-energy phantom was within 4.5%. The average difference of the theoretical and measured Z(eff) values for the acrylic phantom with variation of iodine concentration was within 3.3%. Compared to the results for the single-source Canon-DECT scanner used in our previous study, the average difference and CV of the theoretical and measured Z(eff) values obtained with the GE-DECT scanner were markedly smaller. CONCLUSIONS: The accuracy of the synthesized Z(eff) values with GE-DECT had a good agreement with the theoretical Z(eff) values for the Multi-Energy phantom. The GE-DECT could reduce the noise and the accuracy of the Z(eff) values than that with Canon-DECT for the varying iodine concentrations of contrast medium. ADVANCES IN KNOWLEDGE: The accuracy and precision of the Z(eff) values of the contrast medium with the GE-DECT could be sufficient with human equivalent materials.